Enhancing the Paikem Learning Model's Applicability: The Clinical Supervision Model - Purba, Saut; Parhusip, Akdel (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the increase in the ability of class teachers to implement the PAIKEM learning model through the application of clinical supervision with a collaborative approach at SDS Santa Lucia Sei Rotan. A sample of 10 people was determined based on a purposive sampling technique. The research was conducted in two cycles, each consisting of four stages: planning, implementing activities, observing, and reflecting. Data collection through interviews, observation, and documentation. The study's results concluded: (1) In the pre-cycle, teachers still needed to implement the PAIKEM learning model. (2) In the first cycle, the teacher's ability score to apply the PAIKEM learning model = 52.22 (very low). In the second cycle, the teacher's ability increased significantly, namely 95.46 (very good). (3) Student activity in the first cycle average score = 65 (poor category). There was a fairly high increase in the second cycle, with an average score = of 91.67 (very good). The findings of this study, through the application of clinical supervision with a collaborative approach, can improve the teaching abilities of class teachers with the PAIKEM learning model.